Mechanical properties evaluation and model finite element analysis of cork and felt based nanofilled phenolic resin composites - George PELIN; Camelia MUNTEANU; Cristina-Elisabeta PELIN; Adriana STEFAN; Daniela BARAN (INCAS Bulletin, 2016)
The paper presents the development of numerical experiences using finite element commercial codes, based on experimental mechanical tests performed on ablative composite materials. The studied ablative materials were obtained using liquid phenolic resin matrix nanofilled with silicon carbide nanoparticles (added in different weight contents values: 0, 1 and 2 wt.% relative to the resin) that was impregnated into ablative preforms. The results of the numerical simulations are in accordance with the experimental data obtained for the tested specimens, showing that finite element analysis is a promising tool for development of a realistic simulation for advanced materials used in aerospace applications.